ANALISA KECEPATAN TRANSFER DATA PADA PERANCAGAN HOTSPOT SEDERHANA DENGAN SYSTEM SINGLE SIGN-ON DI PERKANTORAN - Pangesti, Bela Neziah Arum (P3M Politeknik Negeri Banjarmasin, 2017)
The office problems in the utilization of wireless technology widely used but sometimes without calculate the number of users, so it is not efficacious. The networking system for small office can be use wireless simple system. Most of the office has applied hotspot but that is old system ,one account for all people using to internet access. Single sign-on is a System services of hotspot, this system verifying an account for each user so people have different username dan a password. The method used in this research is literature review, analysis, design, implementation, testing and analysis of the data transfer rate. The hotspot with a single sign-on system using mikrotik, and access point that connected to networking devices in the office. The configuration using a winbox tools. The design of the system continued to be tested with an analysis of the data transfer rate (throughput) to upload data using a wireshark tools. The results obtained from this study is the hotspot service with single sign-on system and known types data transfer rate of word files is a greater than file types PDF and PPT